2021
DOI: 10.1177/1556984521997086
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Minimally Invasive Surgery for Mitral Valve Infective Endocarditis

Abstract: Objective The scope of application of minimally invasive mitral valve surgery is expanding. However, the safety and efficacy of minimally invasive mitral valve surgery in the setting of infective endocarditis is not well known. We sought to identify the best evidence available to support a minimally invasive surgical approach for mitral valve infective endocarditis. Methods A systematic review of minimally invasive mitral valve surgery for infective endocarditis was conducted according to the Preferred Reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A recent systematic review of minimally invasive mitral valve replacement in IE showed that in experienced hands, the minimally invasive approach can be successful, has acceptable perioperative morbidity as well as short- and intermediate-term mortality, and should be considered an acceptable alternative to sternotomy in IE of the mitral valve [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of minimally invasive mitral valve replacement in IE showed that in experienced hands, the minimally invasive approach can be successful, has acceptable perioperative morbidity as well as short- and intermediate-term mortality, and should be considered an acceptable alternative to sternotomy in IE of the mitral valve [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive cardiac surgery has consistently evolved during the last few years. To date, also complex valve diseases and high-risk subgroups of patients, such as those with IE, are routinely enrolled for operations using a right mini-thoracotomy approach in experienced heart valve centers [ 11 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MICS allows safety and outcomes comparable to the results after sternotomy, reducing trauma and allowing faster recovery 4 . Minimally invasive approaches are used in several clinical conditions such as functional mitral insufficiency, 5 endocarditis 6 with successful results. MICS is feasible also for the over‐65s and elderly 7 and for high‐risk patients 8 .…”
Section: Discussionmentioning
confidence: 99%